2011
DOI: 10.1242/jeb.055475
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic response to elevated PCO2 level in eastern oysters, Crassostrea virginica: evidence for oxidative stress

Abstract: SUMMARYEstuaries are characterized by extreme fluctuations in CO 2 levels due to bouts of CO 2 production by the resident biota that exceed its capacity of CO 2 consumption and/or the rates of gas exchange with the atmosphere and open ocean waters. Elevated partial pressures of CO 2 (P CO2; i.e. environmental hypercapnia) decrease the pH of estuarine waters and, ultimately, extracellular and intracellular pH levels of estuarine organisms such as mollusks that have limited capacity for pH regulation. We analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(199 citation statements)
references
References 62 publications
12
186
1
Order By: Relevance
“…The role of these antioxidant systems can be of great importance in response to environmental stress in aquatic animals [41]. Previous studies have demonstrated that OA exposure could generally cause oxidative stress in bivalve, sea urchin and coral [37,38,42,43]. In this study, the activities of antioxidant enzymes and GSH and MDA levels in gills did not change significantly on Day 7 and Day 14, suggesting this oyster could maintain its redox homeostasis in gills under elevated pCO 2 exposure levels.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The role of these antioxidant systems can be of great importance in response to environmental stress in aquatic animals [41]. Previous studies have demonstrated that OA exposure could generally cause oxidative stress in bivalve, sea urchin and coral [37,38,42,43]. In this study, the activities of antioxidant enzymes and GSH and MDA levels in gills did not change significantly on Day 7 and Day 14, suggesting this oyster could maintain its redox homeostasis in gills under elevated pCO 2 exposure levels.…”
Section: Discussionmentioning
confidence: 49%
“…However, the effects of OA on the physiological response of mollusks are variable among species and even within the same species [32]. In C. virginica, SOD expression was up-regulated in the mantle tissue of oysters under elevated pCO 2 condition (pH7.5) [42]. In the clam Chamelea gallina and the mussel Mytilus galloprovincialis, OA stress also generally caused increases in antioxidant enzyme activities after exposure for 7 days [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although temperature increases have long been known to impact oxidative stress in organisms (Lesser, 2006), ocean acidification has recently emerged as a potentially more pressing issue in the world's oceans, and to date, we still have a poor understanding of the cellular-level impact that ecologically relevant increases in seawater Ṗ CO 2 will have on cellular homeostasis. Increases in Ṗ CO2 are specifically hypothesized to exacerbate oxidative stress by directly affecting mitochondrial function (Murphy, 2009;Tomanek et al, 2011), and recent studies have indeed shown that hypercapnia can negatively affect mitochondrial capacities in Antarctic fish (Strobel et al, 2012;Strobel et al, 2013b). We found that oxidative damage was most apparent within the first 7 days of acclimation to the treatment conditions, which coincides with a spike in the resting metabolic rate (RMR) of all three species under these same acclimation conditions (Enzor et al, 2013).…”
Section: Tissue-specific Changes In Antioxidant Capacitymentioning
confidence: 58%
“…Decreased oxidative damage in notothenioid fish after long-term acclimation to multiple stressors Laura A. Enzor and Sean P. Place* extent than temperate regions (Walther et al, 2002;Orr et al, 2005;Turner et al, 2005;McNeil and Matear, 2008;Fabry et al, 2008;Fabry et al, 2009;Halpern et al, 2008;McNeil et al, 2010;Mathis et al, 2011a;Mathis et al, 2011b), only a handful of studies have examined the effects of ecologically relevant increases in seawater Ṗ CO 2 on high latitude marine teleosts (Hurst et al, 2012;Strobel et al, 2012;Enzor et al, 2013;Strobel et al, 2013a;Strobel et al, 2013b). Similar to impacts seen with elevated temperature, ocean acidification may also perturb oxidative stress in marine teleosts (Murphy, 2009;Tomanek et al, 2011) and may even exacerbate the detrimental effects of reactive oxygen species at the cellular level (Ezraty et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Britz et al [18] and Hooper et al [19] reported that high temperature of over 20°C has been shown to cause immunosuppression, reduced growth, heat shock to protein in abalone during summer season and could lead to serious disease outbreak. Tomanek et al [20] demonstrated that pH of 7.5 can cause oxidative stress in Crassostrea virginica. This is supported by Matozzo et al [21] who showed that decreased pH and high temperature can strongly affect the immune-parameters of clam, Chamelea gallina and mussel, Mytilus galloprovincialis.…”
Section: Introduction and Justification Of Studymentioning
confidence: 99%